Konstruksi Sosial Stigma Anak Berkebutuhan Khusus dalam Pendidikan Inklusif di Kota Makassar - Nurazizah Rahmi R.; Asmaul Husnah Amiruddin; M. Dissha Najiah Al Yas'a (Universitas Methodist Indonesia, 2026)
This study analyzes the social construction of stigma against children with special needs within the inclusive education system of Makassar City using a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol. Grounded in Goffman's stigma theory, labeling theory (Becker, 1963), and Berger and Luckmann's social construction framework (1966), this study examines how stigma is produced, reproduced, and negotiated at three levels: family, school institutions, and the Bugis-Makassar cultural community. A total of 24 verified sources from 2016 to 2025 were analyzed using a thematic-interpretive method. Findings reveal that stigma against ABK is multidimensional, shaped by the dialectics of Siri' na Pacce cultural values where Siri' reinforces stigmatization while Pacce holds potential to deconstruct it alongside structural deficiencies in inclusive education institutions and weak social protection mechanisms in schools. The viral bullying case at SMPN 4 Makassar (2024) serves as an empirical reflection of this systemic failure. This study recommends a local wisdom-based inclusion model integrating Sipakatau and Pacce values as the ethical foundation for inclusive education policy in Makassar.